Design and Construction of Electrical Energy Source Panel Based on Thermoelectric Generators on Mild Steel Galvalume - Maulana, Bima Wahyu; Misto, M.; Arkundato, Artoto; Mulyono, Tri (Jurnal ILMU DASAR, 2023)
A thermoelectric generator (TEG) is a device that converts heat energy into electrical energy. The working principle of this device is based on Seebeck's law, namely this device will produce electrical energy if the cold side and hot side of this device have a temperature difference value of . This device can be used for generator panels whose heat source comes from the sun. The cold side of the TEG is conditioned by utilizing water fluid which is passed over the heatsink. The temperature difference between the hot and cold sides of the TEG generates an electric voltage through the Seebeck effect. The parameters observed in the research on electricity generation using this TEG are voltage, current, electric power, and the temperature difference between the hot and cold sides. The resulting parameter values are as follows; average voltage (0.5495 volts), average electric current strength of 0.04 A, average electric power (0.022 watts). mean temperature difference (16.006 oC). The largest average Seebeck coefficient is 0.0413 V/oC.